Evaluasi User Experience Pada Edmodo Dan Google Classroom Menggunakan Technique for User Experience Evaluation in E-Learning (TUXEL) (Studi Pada SMKN 5 Malang) - Dini Nurhayati; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This study aims to discuss user experience of Edmodo, Google Classroom, and compare user experience both of them. As well as providing suggestions for using Edmodo or Google Classroom. For this reason, researcher evaluated the user experience using Techniques for User eXperience Evaluation in e-Learning (TUXEL), in which there are three aspects inside, general usability, pedagogical usability, and user experience. The study was held in Vocational High School 5 Malang with 24 respondents. The results of this study on the general usability aspects, Edmodo found 9 problems and Google Classroom 12 problems. In the pedagogical usability aspects, Edmodo found 13 problems, and 15 problems in Google Classroom. On the aspect of user experience, Edmodo identified the following code: (1) supportive; (2) confusing; (3) complicated. As for the Google Classroom, that is the following code: (1) practical; (2) pleasing; (3) does not meet expectations; (4) confusing. The conclusion is, Edmodo is suitable for the learning process that uses full online learning, while Google Classroom is more suitable to be used as supporting / complementary learning.